Environmental Determinants, Entrepreneurial Orientation and Export Performance: Empirical Evidence from Iran - Jalali, Seyed Hossein (Serbian Journal of Management, 2012)
This study empirically examined the relationship between entrepreneurial orientation (EO) and export performance through a model in which environmental dynamism, hostility and uncertainty play an antecedent role for EO. The questionnaire of the study was applied to 183 decision makers in charge of exports in Iranian SME's in food industry, which regularly export their products to Eastern European countries. Structural equation modeling technique was used to analyze the gathered data. The finding from analyses support the conceptual framework of the study and obtained results indicated that innovativeness, as one of the EO dimensions, is the most effective strategy for SME's and help them to deal with the turbulent environmental condition and improve their export performance.